Enhanced salt sensitivity following shRNA silencing of neuronal TRPV1 in rat spinal cord - Yu Shuang-quan; Wang Donna H (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of selective knockdown of TRPV1 channels in the lower thoracic and upper lumbar segments of spinal cord, dorsal root ganglia (DRG) and mesenteric arteries on rat blood pressure responses to high salt intake. Methods: TRPV1 short-hairpin RNA (shRNA) was delivered using intrathecal injection (6 μg·kg−1·d−1, for 3 d). Levels of TRPV1 and tyrosine hydroxylase expression were determined by Western blot analysis. Systolic blood pressure and mean arterial pressure (MAP) were examined using tail-cuff and direct arterial measurement, respectively. Results: In rats injected with control shRNA, high-salt diet (HS) caused higher systolic blood pressure compared with normal-salt diet (NS) (HS:149±4 mmHg; NS:126±2 mmHg, P